Employment dynamics, increasing returns and Marx’s falling rate of profit - Padhi, Satya Prasad (PSL Quarterly Review, 2021)
It is assumed that Marx focuses on profits that are to be realized in larger production that permits some surplus production. This understanding underpins the importance of increasing returns embedded in employment dynamics associated with larger employment bases. This organizational form not only permits increases in profits in production but also supports employment-based learning by doing-led new investment opportunities that maintain and increase such profits. The conception of profits changes from the employment dynamics-based one, to one that relies more on market power-based returns. Accordingly, the present paper argues that empirical analyses should not focus on a falling rate of profits as such: they should rather focus on what factors make clear the behaviour of the rate of profit, and clearly distinguish between the employment dynamics-based profits and the profits that relate more to the returns to higher fixed costs. JEL codes: B5, E11, O14, P17